IMPLEMENTATION OF COLD CHAIN SYSTEM IN FROZEN POCKET YELLOWFIN TUNA (Thunnus albacares) - Napitupulu, Romauli Juliana; Hasna, Hanifah; Panjaitan, Pola S. T (Politeknik Kelautan dan Perikanan Dumai, 2025)
Cold chain systems are essential in maintaining the quality and safety of frozen fishery products, particularly yellowfin tuna, which has high economic value. This study evaluates the implementation of the cold chain system in the production of frozen yellowfin tuna saku at a processing company. The research was conducted using a descriptive method through direct observation and temperature monitoring across all stages of the cold chain, including receiving of raw material, processing, and cold storing. Temperature measurements were conducted on tuna, water, and processing rooms, using three tuna samples per observation, with triplicate measurements for each sample. The results demonstrated that tuna temperatures remained below the Indonesian regulatory limit of 4.4°C throughout processing, with raw material temperatures averaging 2.4 ± 0.76°C. Water temperatures during temporary storage averaged 3.5°C, while washing water ranged from 25–27°C. Room temperatures across processing areas were maintained between 22–23°C, complying with the company’s standard maximum of 25°C. The Air Blast Freezer (ABF) operated at –35 to –38.9°C, with an average of –37.76 ± 1.12°C across ten weeks, surpassing both company and national standards (≤ –18°C). Cold storage temperatures ranged from –20°C to –30°C, maintaining the product core temperature at –18°C. Although overall temperature control complied with required standards, the findings indicate the need for more stringent temperature monitoring to minimize fluctuations at several critical stages. The study concludes that the cold chain system is effectively implemented, but improvements in consistent temperature stability are necessary to further prevent quality degradation.